2011
DOI: 10.1111/j.1553-2712.2011.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Research Priorities for High-quality Geriatric Emergency Care: Medication Management, Screening, and Prevention and Functional Assessment

Abstract: Background Geriatric adults represent an increasing proportion of emergency department (ED) users, and can be particularly vulnerable to acute illnesses. Health care providers have recently begun to focus upon the development of quality indicators to define a minimal standard of care. Objectives The original objective of this project was to develop additional ED-specific quality indicators for older patients within the domains of medication management, screening and prevention, and functional assessment, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 110 publications
0
67
0
4
Order By: Relevance
“…11,12 Consequently, geriatric and emergency medicine research opinion leaders list development and implementation trials of prognostic screening instruments among the highest research priorities. 13,14 This systematic review helps define the accuracy of existing screening tools to identify older ED patients at risk of adverse outcomes. Four recent systematic reviews evaluate the content validity and prognostic accuracy of single geriatric screening instruments such as the Triage Risk Screening Tool (TRST), [15][16][17][18] but none of these systematic reviews evaluates all available instruments or all previously described individual risk factors for post-ED adverse outcomes.…”
mentioning
confidence: 99%
“…11,12 Consequently, geriatric and emergency medicine research opinion leaders list development and implementation trials of prognostic screening instruments among the highest research priorities. 13,14 This systematic review helps define the accuracy of existing screening tools to identify older ED patients at risk of adverse outcomes. Four recent systematic reviews evaluate the content validity and prognostic accuracy of single geriatric screening instruments such as the Triage Risk Screening Tool (TRST), [15][16][17][18] but none of these systematic reviews evaluates all available instruments or all previously described individual risk factors for post-ED adverse outcomes.…”
mentioning
confidence: 99%
“…Kennzahlen und Qualitätsindikatoren hierfür sind in der internationalen Literatur bislang unterrepräsentiert [22][23][24]. Lediglich für einzelne Teilbereiche, wie z.…”
Section: Der Anspruch -Qualitätunclassified
“…Papers were selected on the basis of their relevance to developing competencies in GEM by agreement between a geriatrician and an emergency physician. A range of articles including North American initiatives to develop a GEM curriculum and recent reviews and key articles in the field were identified and used to inform the development of the domains and items [7][8][9][10][11][12][13][14][15][16][17] . The development focused upon the additional competencies over and above that which would be expected from training in either geriatric medicine or emergency medicine -so this was not simply a reproduction of how to practice emergency medicine in older people, but an attempt to develop higher level competencies that will add value to existing curriculae 7 .…”
Section: Review Of the Literaturementioning
confidence: 99%